1982
DOI: 10.3109/00365598209179749
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocyte and Albumin Distribution in the Kidney Following Warm Ischemia

Abstract: A dark zone of probably stagnant erythrocytes, localised primarily to the inner stripe of the outer medulla, is always found in acute renal failure caused by clamping of the renal artery for 45 min. To test the possible accumulation of red cells, the regional renal red cell content was investigated with 51Cr labelled red cells injected before, during and 10 min after the recirculation. Analyses were made of the volumes of (1) cells remaining from the period of clamping, (2) cells aggregated 0--10 min after rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
0

Year Published

1982
1982
1995
1995

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 13 publications
3
23
0
Order By: Relevance
“…Previous studies have indicated that the RBC trapping occurs either during ischaemia [5,10] or in the very early recirculation phase [9,14], and disappears within less than 24 h [10,14]. It is evident from the results for the contra lateral intact kidneys in the present study that mannitol per se does not induce RBC trap ping.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Previous studies have indicated that the RBC trapping occurs either during ischaemia [5,10] or in the very early recirculation phase [9,14], and disappears within less than 24 h [10,14]. It is evident from the results for the contra lateral intact kidneys in the present study that mannitol per se does not induce RBC trap ping.…”
Section: Discussionsupporting
confidence: 56%
“…The cell-labelling procedure has been described previously [9], Briefly, blood was collected in an acid-citrate-dextrose solution and cen trifuged. The plasma and 'huffy coat' were removed.…”
Section: Methodsmentioning
confidence: 99%
“…In ischaemic kidneys, red blood cells become trapped within the microvasculature of the outer medulla [26][27][28][29][30][31][32]. Reperfusion is clearly dependent upon the number of red blood cells trapped and their speed of clearance.…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon can be explained by a leakage of plasma fluid and proteins in the glomeruli and peritubular capillaries. The leakage of proteins might be of importance in the development of casts with subsequent tubular obstruction both in pa tients with ARF and in experimental RAO [Racusen et al, 1982], This exudation of plasma may also be responsible for the raised hematocrit value and red cell stagnation in the vasa recta and thus for the diminished perfusion in the outer medulla after RAO [Karlberg et al, 1982], Such changes at an early stage of the renal damage could be of importance for the development of the persistent impair ment of renal function. In other organs substances libe rated during the coagulation process have been shown to possess permeability-increasing properties.…”
Section: Introductionmentioning
confidence: 99%